2015
DOI: 10.1021/jm5019302
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CDDO–Amino Acid–Nitric Oxide Donor Trihybrids as Potential Antitumor Agents against Both Drug-Sensitive and Drug-Resistant Colon Cancer

Abstract: Seventeen CDDO-amino acid-NO donor trihybrids (4a-q) were designed and synthesized. Biological evaluation indicated that the most active compound 4c produced high levels of NO and inhibited the proliferation of drug-sensitive (HCT-8, IC50 = 0.294 μM) and drug-resistant (HCT-8/5-FU, IC50 = 0.232 μM) colon cancer cells, which were attenuated by an NO scavenger or typical substrate of PepT1. Furthermore, 4c triggered HCT-8 and HCT-8/5-FU cell apoptosis more strongly than CDDO-Me, inhibited the HIF-1α, Stat3, AKT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…The bound antibodies were detected by horseradish peroxidase (HRP) conjugated second antibodies and visualized using an enhanced chemiluminescent reagent. The relative levels of each signaling event to control GAPDH were determined by densimetric scanning [20,29,40].…”
Section: Western Blotting Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The bound antibodies were detected by horseradish peroxidase (HRP) conjugated second antibodies and visualized using an enhanced chemiluminescent reagent. The relative levels of each signaling event to control GAPDH were determined by densimetric scanning [20,29,40].…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…In recent decade, numerous efforts were directed towards the construction of hybrids incorporating furoxan subunits to advance the pharmacological profile of the parent drug. Many studies have shown that (phenylsulfonyl)furoxanbased NO-releasing natural products possessed greater antitumor activity than corresponding parent compounds, furoxan precursors and/or their combinations in vitro and in vivo [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), one of the simplest, odorless, colorless, highly reactive, and biological molecules in nature, is a free radical and a key mediator involved in diverse physiological and pathological processes [16][17][18][19][20]. NO-donating compounds have recently come into focus for the treatment of tumors because NO plays a central role in cell regulatory pathways and is a key signaling molecule involved in the death and apoptosis of tumor cells [21][22][23][24][25][26][27][28][29][30][31][32]. Generally, high levels of NO (above 400 nM [33]) produced from NO donors can induce apoptosis, inhibit metastasis of tumor cells, and sensitize tumor cells to radiation, immunotherapy, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, high levels of NO (above 400 nM [33]) produced from NO donors can induce apoptosis, inhibit metastasis of tumor cells, and sensitize tumor cells to radiation, immunotherapy, and chemotherapy. Some synthesized NO-releasing compounds have already shown antitumor activity against human carcinoma cells in vitro and in vivo [21][22][23][24][25][26][27][28][29][30][31][32]. Due to the highly reactive nature of NO, it is difficult to predict its biological effects on a given system from single doses even if provided by the longer action of inducible nitric oxide synthase (iNOS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation